THE CORRELATION BETWEEN EMPLOYEE ENGAGEMENT AND PERFORMANCE AT A RETAIL INDUSTRY IN DELHI. - Pandey, Devashish; Kaplash, Sanket; Sarkar, Divya (The journal of contemporary issues in business and government, 2022)
The study revealed the realities about staff engagement strategies used in Delhi's retail sector. Initiatives to increase employee engagement are thought to be a useful tactic for success, The goal of the study is to determine how engaged employees are with their workplaces and how it affects their overall productivity. To understand the effect of engagement on performance, several factors are used. The idea is that employee engagement motivates workers to increase organisational performance, decrease attrition rates, enhance their health, and feel better about going to work. Total (112 respondents) were selected as the population. As per secondary, several factors affect employee engagement, and effective engagement methods are crucial to the profitability of the retail industry as well as the professional development of workers.